Indigenous Festivals in Australia: Performing the Postcolonial. Issue 4 (7th August 2016) - Phipps, Peter
ABSTRACT: Indigenous festivals can be a potent site for cross-cultural negotiations of meaning, and spaces where indigenous people can actively represent themselves and their cultures in a positive light. These events can also provide models and opportunities for fuller indigenous social, political and economic participation on indigenous terms [Phipps, Peter & Lisa Slater. 2010. Indigenous Cultural Festivals: Evaluating Impact on Community Health and Wellbeing. Report to Telstra Foundation, RMIT Globalism Research Centre. http://rmit.edu.au/globalism/publications/reports (ISBN 978-0-9805531-8-5)] and challenge hegemonic notions of sovereignty in a settler–colonial society [Phipps Peter 2010. 'Performances of Power: Indigenous Cultural Festivals as Globally Engaged Cultural Strategy'. Alternatives: Global, Local, Political, 35(3); 2011. Performing Culture as Political Strategy: The Garma Festival, Northeast Arnhemland. In Festival Places: Revitalising Rural Australia, edited by Gibson Chris and John Connell. pp. 109–122. Bristol: Channel View Publications]. Along with the visual arts, festivals are one of the few consistently positive spaces for Australian Indigenous communities to show themselves and the world a more affirming view of their cultures and identities.